UJI DAYA HAMBAT EKSTRAK KULIT BUAH PISANG KEPOK (Musa paradisiaca forma typica) TERHADAP Shigella dysenteriae DAN Salmonella typhi - Novia Ariani; Rakhmadhan Niah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
One global problem that is being faced is one of the side effects of antibiotic use in both developing and developed countries so that some actions need to be taken to overcome the global problems that are happening. One effort that is being carried out is to look for alternative treatments with active compounds that come from nature. One plant that has antibacterial properties is kepok banana skin with the scientific name Musa paradisiaca. The purpose of this study was to determine the presence or absence of inhibitory zone activity and inhibitory classification of kepok banana peel extract against the bacteria Shigella dysenteriae and Salmonella typhi. This type of research is an experimental research with a well method that was conducted at the microbiology laboratory Akademi Farmasi ISFI Banjarmasin. The sample used was raw kepok banana from Desa Jaro who meets the criteria. Extraction method used is maceration with 96% ethanol. This study is divided into 2 main groups, namely extract group and negative control. The inhibition zone that is formed is measured using a caliph run. The results showed that Kepok banana peel extract with a concentration of 10% had inhibitory power on the bacteria Shigella dysenteriae and Salmonella typhi with a strong inhibitory classification.